Analyzing the Spatial Impact of Population Growth and its Impact on Current and Future Urban Land Uses Najaf Center, a Case Study for the Period 2022-2027 (Journal of University of Babylon for Engineering Sciences, 2024)
The city is characterized by a variety of urban land uses, housing, roads, commerce, industry, various services, green and open areas, expressed public spaces, the city is developing and expanding urbanely under the influence of population growth. Its location may allow it to expand in several directions until it reaches the limit that prevents its expansion, especially in the neighborhoods of city centers, so it searches for other alternatives to expansion. The problem begins when the population grows rapidly and we do not find areas that meet human needs from standard land uses. The study aims to analyze the relationship between population growth, normative urban expansion, and the reality of the situation in the district center, to identify land uses, size, and its trends. The study relied on the historical and descriptive analytical method, the study showed that the spatial reality of the urban land uses of the study area grew under the pressure of population growth, but it did not conform and did not meet the standard spatial need for all urban land uses, and in most neighborhoods the spatial need recorded a negative number.